2013
DOI: 10.2105/ajph.2012.301165
|View full text |Cite
|
Sign up to set email alerts
|

Designing for Dissemination Among Public Health Researchers: Findings From a National Survey in the United States

Abstract: The current data and the existing literature suggest considerable room for improvement in designing for dissemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
286
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(294 citation statements)
references
References 40 publications
8
286
0
Order By: Relevance
“…As a result, the original reason for choosing evidence-based interventions-to assure that they will have an impact when implemented-is often thwarted because these interventions are designed to achieve evidence of impact alone rather than to promote implementation at the practice level. Very few programs are "designed for dissemination" (9,45) such that they are scalable from the beginning, which is essential for true public health impact. To address this problem, researchers and practitioners are forming partnerships to generate practice-based evidence.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the original reason for choosing evidence-based interventions-to assure that they will have an impact when implemented-is often thwarted because these interventions are designed to achieve evidence of impact alone rather than to promote implementation at the practice level. Very few programs are "designed for dissemination" (9,45) such that they are scalable from the beginning, which is essential for true public health impact. To address this problem, researchers and practitioners are forming partnerships to generate practice-based evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Share results with participants and community partners-At important study milestones, we individually sent result summaries to and thanked our research participants and community partners. Although some researchers see sharing research results with participants as an ethical obligation, Brownson's recent study of dissemination among public health researchers found that only one third of researchers always or usually produced summaries for non-research audiences [22,23]. Our strategy required minimal staff time and was a quick way to send our results to thousands of women and healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…One qualitative study suggests that for research to impact practitioners, at least 12 % of project resources and time should be dedicated to dissemination [24]. However, Brownson's study also reported that 73 % of the respondents estimated spending less than 10 % of their time on dissemination and only about half had a person or team dedicated to dissemination [23]. Without a CHOICE staff position dedicated to CE&D, progress would have been minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Political support, funding agency priorities, capacity of the dissemination organization, and knowledge of researchers in how to apply research findings can influence the success of study translation [20][21][22][23]. Although many researchers have dissemination expectations from funders [20], the majority of public health professionals spend little time and efforts on program dissemination [24], and few studies reported sustainability and challenges of disseminating an online decision aid tool from an effective intervention study. To address this gap, we examined the use of the SMHP tool during its dissemination to the general public in Missouri and compared this with use of the tool during the randomized controlled trial.…”
Section: Introductionmentioning
confidence: 99%